IMPLEMENTASI E-COURT SEBAGAI WUJUD PELAYANAN PENGADILAN YANG SEDERHANA, CEPAT DAN BIAYA RINGAN - Ansek, Jeklin Patresia; Belekubun, Angelina A. Gracia; Mursidin R, Fathlia; Silubun, Yosman Leonard; silubun, yosman (Animha Law Journal, 2024)
ABSTRACT E-Court is an instrument in court as a form of service to the public in terms of online case registration, online payments, online summons, and online trials. Meanwhile, before the existence of the E-Court, people tended to experience difficulties in carrying out court activities because people had to go to the previous court which would take a lot of time and money, this is what led to a lack of efficiency and effectiveness of services in case registration and trial processes. Seeing the community's difficulties, E-Court was launched based on Supreme Court regulations which are useful for making it easier for the public to carry out court activities using technology which saves time and excessive costs in order to realize the ideals of efficient and effective public services. This research aims to determine the implementation of e-court in services at the Merauke City District Court. The method used in this research is an empirical legal research method. The implementation of e-court in Indonesia is an innovation that aims to speed up and facilitate the trial process in court. Users can register cases online via the e-court application. This makes it easier for litigants to handle their cases without needing to come directly to court Keywords: Implementation of E-Court, District Court, Simple, Fast, Low Cost